KAJIAN FREKUENSI DAN LAMA PEMAPARAN MEDAN ELEKTROMAGNETIK PADA FASE GENERATIF TERHADAP PRODUKSI DAN KUALITAS BUNGA KRISAN (Crhysantemum) - I Made Wirawan Suputra; I Made Anom. S. Wijaya; I Wayan Tika (Jurnal BETA (Biosistem dan Teknik Pertanian), 2015)
The objectives of this research were to (1) determine the production and quality of chrysanthemum on frequency (amount of exposure per day) and duration of electromagnetic field exposure during generative phase, (2) determine frequency and duration of electromagnetic field exposure which produce the best production and quality of chrysanthemum flower. The method of this research was experimental method with two treatments. The first treatment was frequency of electromagnetic field exposure consisted of 1, 2 and 3 times per day and second treatment was electromagnetic field exposure duration consisted of 5, 20, and 35 minutes. Variables which measured for flower production were age of plant that started to blooming, harvest age, amount of flower and amount flower of half blooming, while for quality were diameter of flower, flower color, weight flower, and flower resistance after harvest. Result showed that production and quality of chrysanthemum was low, if electromagnetic field exposure at 3 mT (militesla) with frequency exposure 1, 2 and 3 times per days and duration exposure was 5, 20, and 35 minutes in generative phase. The best treatment contained in frequency 2 time per day and exposure duration 5 minutes gave the best result for production and quality of chrysanthemum flower.